Handbook of human rights - Cushman, Thomas (Routledge international handbooks, 2014)
"In mapping out the field of human rights for those studying and researching within both humanities and social science disciplines, the Handbook of Human Rights provides not only a solid foundation for the reader who wants to learn the basic parameters of the field, but also promotes new thinking and frameworks for the study of human rights in the twenty-first century. The Handbook comprises of nearly sixty individual contributions from key figures around the world, which are grouped according to eight key areas of discussion: - foundations and critiques - new frameworks for understanding human rights - world religious traditions and human rights - social, economic, group and collective rights - critical perspectives on human rights organizations, institutions, and practices - law and human rights - narrative and aesthetic dimension of rights - geographies of rights In its presentation and analysis of the traditional core history and topics, critical perspectives, human rights culture, and current practice, this Handbook proves a valuable resource for all students and researchers with an interest in human rights."